Screening of LDLR, APOB and TNNI3 Genes in Cardiovascular Patients in the Population of Indian Origin - Abrar Ahmad, Syed; Urade, Prachi; Khaliq, Nahida; Chavan, Chandrakant; Wankhade, Varsha (International Journal of Psychosocial Rehabilitation, 2019)
Background: CVD accounts for 31% of mortality, the majority of this in the form of CHD and cerebrovascular accident, the majority of this in the form of CHD and cerebrovascular accident. Methods: Institutional Human Ethics Committee approval was taken for the current study from Bharti Hospital and Savitribai Phule Pune University. DNA was extracted from whole blood, and PCR conditions were optimized for all exons. SSCP was done for screening of variations in all the exons of the APOB, LDLR, and TNNI3 genes. Samples showing abnormal band shifts with respect to control were Sanger sequenced for confirmation of variation. Biochemical estimations were done by commercially available kits. Results: SSCP analysis reveals a band shift in exon 05 of the APOB gene with respect to control samples on 8% gel concentration in proband 16, while other exons of the APOB gene did not show any band shift with respect to control samples. T>G transversion at Chr. Location 55663368 of the intraonic variant was located in exon 08 of proband 13 by screening of all exons of the TNNI3 gene. Sequences revealed. Patient showing G/A variation shows LVEF of 47%, while CVD patients without variation show 43%. The level of NO in control was lower than the MI level and IHD level, but MI patients show the highest level of NO. Conclusion: A reported silent mutation was found in the intronic region without impact on splicing. This variation did not show a profound impact on physiological complication as compared to mutation-negative probands